Analisis Kimia dan Sensoris Kerupuk Ikan yang Dikeringkan dengan Pengering Efek Rumah Kaca (ERK) - Husni Mahfuz; Herpandi Herpandi; Ace Baehaki (Universitas Sriwijaya, 2017)
Research was conducted to know sensory and chemical characteristic of fish crackers dried with dryer greenhouse effect. This research was used survey and laboratory method. It is observing fish crackers dried process used dryer greenhouse effect modified of air sirculations. The result of chemical analysis (water content, ash content, protein, fat, and carbohydrate) showed that H1 (first day) has higer water content and H3 (third days) has higest of mineral, protein, fats, and carbohydrate on inside room themperature 42.38 °C – 42.89 °C, and humidity 40%. Result of sensory test used paired comparation test is not differently between greenhouse effect H2 and H3 crakers with control on 1% level. But color of greenhouse effect crackers with control is different on 1% level. Color of greenhouse effect crackers whiter than control